2020
DOI: 10.1101/2020.08.06.234674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural analysis of full-length SARS-CoV-2 spike protein from an advanced vaccine candidate

Abstract: Vaccine efforts against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) responsible for the current COVID-19 pandemic are focused on SARS-CoV-2 spike glycoprotein, the primary target for neutralizing antibodies. Here, we performed cryo-EM and site-specific glycan analysis of one of the leading subunit vaccine candidates from Novavax based on a full-length spike protein formulated in polysorbate 80 (PS 80) detergent. Our studies reveal a stable prefusion conformation of the spike immunogen with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 61 publications
2
78
0
2
Order By: Relevance
“…In contrast to the structural differences described above for S-2P protein, both of our WT and MT S-Trimer were nearly identical to the recently published structures of full-length wild-type S (PDB ID: 6XR8 ) (11) and 3Q-2P-FL with two proline mutation (PDB ID: 7JJI) (7,14) purified in detergent from HEK293 and sf9 insect cell membranes, respectively. When (Fig.…”
Section: Conformational Change Of the S Protein Before Receptor Bindingsupporting
confidence: 81%
See 3 more Smart Citations
“…In contrast to the structural differences described above for S-2P protein, both of our WT and MT S-Trimer were nearly identical to the recently published structures of full-length wild-type S (PDB ID: 6XR8 ) (11) and 3Q-2P-FL with two proline mutation (PDB ID: 7JJI) (7,14) purified in detergent from HEK293 and sf9 insect cell membranes, respectively. When (Fig.…”
Section: Conformational Change Of the S Protein Before Receptor Bindingsupporting
confidence: 81%
“…Although both oleic acid and linoleic acid can be ambiguously fitted into the density of the RBD region owing to the excellent quality of EM map, mass spectrometry analysis indicated both MT and WT samples contained a higher level of oleic acid than linoleic acid (Fig 4B and 4C). Recent studies revealed the presence of linoleic acid at the same binding site but with slightly different position (7,12). The oleic acid in our structure located in the hydrophobic pocket of the RBD domain engaged a salt bridge interaction with R408 and a hydrogen bond interaction with Q409 at the adjacent protomer through its carboxylic acid group, bringing the RBD domain in close proximity and resulting in the tightly closed conformation (Fig.…”
Section: Downloaded Frommentioning
confidence: 73%
See 2 more Smart Citations
“…Only the V367F mutation was found to be exposed to solvent and was therefore not considered for inclusion in stabilized RBD designs to avoid the risk of unfavorably altering antigenicity. The other four mutations were observed to be near or within a recently identified linoleic acid-binding pocket formed between adjacent RBDs in the closed Spike trimer (71,72), with Y365 identified as a key gating residue for this interaction (Figure 1A-B). The improved expression and stability observed by DMS for several mutations in the linoleic acid-binding pocket suggested that this region is structurally suboptimal in the isolated RBD.…”
Section: Resultsmentioning
confidence: 91%